Australia as US Client State: The Geopolitics of De-Democratization and Insecurity - Paul, Erik.; SpringerLink (Online service). (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book explores Australia's role as a US client state and the subsequent consequences for Australian democracy. Examining whether neoliberal and neoconservative interests have hijacked democracy in Australia, Paul questions whether further de-democratisation will advance US economic and military interests.
Keywords: Science; Science; Science, general